THE EFFECT OF SUPERVISION, INTEGRITY AND TRUST ON PUBLIC JUNIOR HIGH SCHOOL TEACHERS’ WORK EFFECTIVENESS IN CENTRAL JAKARTA REGION - Mardiana, Rita; Abdullah, Thamrin; Akbar, Maruf (JERAM, 2017)
The research was motivated by the marks of Junior High School students from Central Jakarta are lower than other students from other Jakarta areas, which is suspected as the impact of the lack of effectiveness of teacher’s work. This research aims to determine whether or not the influence of supervision, integrity and trust on the effectiveness of teachers in Public Junior High School in Central Jakarta region. Survey method was used with quantitative research using path analysis to analyze the influence of one variable to other variables. The sample in this research were 114 teachers with civil servant status at Public Junior High School  in Central Jakarta region which was taken at random. The results of data analysis show that supervision, integrity, and trust have a direct positive effect on the effectiveness of teachers of Public Junior High School in Central Jakarta region.